"Warm Arctic‐Cold Siberia" as an Internal Mode Instigated by North Atlantic Warming. Issue 9 (25th April 2020) - Jin, Chunhan; Wang, Bin; Yang, Young‐Min; Liu, Jian
Abstract: Eurasia has experienced more frequent bitter winters over the past two decades, which concurred with a prominent "Warm Arctic‐Cold Siberia" (WACS) pattern that is unexpected from global warming. Here we show, by analysis of 117‐year observations and climate model's millennial simulations, that the WACS is an internal mode of winter temperature variability, which cannot be excited by greenhouse gases and solar forcing. Observational and simulated results suggest that frequent occurrences of that WACS pattern are instigated by warm phases of Atlantic Multidecadal Oscillation (AMO). North Atlantic warming may activate the WACS by generating a background Atlantic‐Eurasian wave train characterized by enhanced Ural Mountain ridge and East Asian trough, which is conducive to recurrent WACS pattern. The wave train‐induced the Barents Sea ice melting can act as an amplifier, reinforcing the WACS. Although increased greenhouse gases favor a uniform warming pattern, they may contribute to WACS formation by affecting AMO. Plain Language Summary: During the past two decades, Eurasia has experienced frequent bitter winters against the rapid warming over the Arctic, which have caused severe damage to livelihoods and socio‐ecological systems. The prevailing paradigm attributes cold Eurasia to accelerated Barents‐Kara Sea ice melt as part of global warming. Here we show, by analysis of 117‐year observations and climate model's millennial simulations, that the WACS is an internal mode of winter temperature variability instigated by a warm phase of Atlantic Multidecadal Oscillation (AMO). North Atlantic warming stimulates the WACS by generating a background planetary wave train that is conducive to the frequent occurrence of the WACS. Although increased greenhouse gases favor a uniform warming pattern, they may contribute to WACS formation by affecting AMO. The findings deepen our understanding of the interactive influences of natural variability and anthropogenic forcing on climate change and shed light on future change of northern winter climate under increasing anthropogenic forcing. Key Points: The "Warm Arctic‐Cold Siberia" (WACS) pattern is an internal mode of variability, which cannot be excited by GHGs and solar forcing Observational and simulated results suggest that the frequent occurrence of the WACS pattern is instigated by the warm phase of AMO Warm Atlantic generates an Atlantic‐Eurasian wave train that enhances Ural Mountain ridge and East Asian trough, causing the WACS pattern